Le cadre de management du tourisme intelligent - Shiwei Shen; Marios Sotiriadis (Études Caribéennes)
Digital technology (information and communication technologies) has developed at an unprecedented rate, fundamentally changing and continuing to transform the way we live. In the last two decades, we are witnessing the convergence of the physical and digital worlds, supported by sensors collecting data from the mutual interactions between tourists and venues/destinations. Intelligent tourism (IT) is one of the digital applications shaping the current and future business environment (Gretzel et al., 2015a, Zhang & Yang 2016). The advancement of information and communication technologies (ICT) in general, and cloud computing technologies in particular, is driving tourism destinations and providers to leverage smart technologies to optimize their decision-making, strategic planning, and improve the tourism experience for visitors. The term 'IT' refers to the growing phenomenon of applying ICT and digital technologies to develop approaches and tools to improve tourism and travel activities (Ye et al., 2020).